Consideration of Semarang District Court Judge's Decision in Case Dropped Because The Crime of Defense of Emergency - Zulfikar Hanafi Bahri (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This study aims to determine the basic consideration of the judge and the factors that influence their consideration of the judge in the verdict against perpetrators of criminal acts because of a defense emergency, given the motivation offenders who commit criminal acts solely for self-defense, and the factors that influence consideration of the judge in the verdict against the accused, so it took the foresight of the judges who handle it and the basis and reasoning of judges itself in implementing its decision. In completing this study, the authors use a step to find data and collect data either through the study of literature and other data sources and to analyze the subject and object data obtained through empirical juridical approach, while sampling was conducted through interviews with directional type. Based on research by the author in the location, it can be authors conclude that consideration of the judge in the verdict against perpetrators of criminal because of a defense emergency in addition based on the provisions of the Act, namely Article 49 of the Code of Criminal Law, taking into account factors about the motives of the accused in criminal offense must be solely for self-defense, so that when the verdict, can be justified by fair in accordance with the legislation and of course also the aspect of sociological and psychological defendant, to obtain a ruling that can be justified legally, morally, and religion by the judge.Keywords: Consideration; Justice; Defense; Emergency.